Neuroscience Perspectives on Religious Moderation: An Analysis of Muhammadiyah's Fatwas in Response to the Covid-19 Pandemic - Waharjani, Waharjani; Jailani, Mohammad (Cakrawala: Jurnal Studi Islam, 2024)
This study examines how neuroscience can enrich our understanding of religious moderation, particularly in the context of the COVID-19 pandemic. Focusing on Muhammadiyah's fatwas, this research aims to understand how a neuro-religious approach can support the implementation of moderation principles in religious practices. Through a qualitative analysis of relevant literature, this study finds that Muhammadiyah's fatwas during the pandemic emphasized the importance of balance between faith and reason in addressing public health challenges. Neuroscience provides a scientific foundation for understanding how the human brain processes religious information and how moderation can be promoted through cognitive mechanisms. The results show that Muhammadiyah's fatwas not only provide practical guidance for worship during the pandemic but also encourage the development of a moderate attitude rooted in a deeper understanding of Islamic teachings. This study concludes that the integration of neuroscience and Islamic studies can contribute to the development of a more comprehensive framework for promoting religious moderation in the future.